Penerapan Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange Terhadap Keterampilan Kooperatif dan Hasil Belajar Siswa pada Materi Momentum dan Impuls - Yesinta Heliyandari; Mukhlis Rohmadi; Hadma Yuliani (Universitas PGRI Semarang, 2018)
This study was aimed to know: (1) Whether there is or no increase of cooperative skill and whether there isi or no increas of students’ learning outcomes who participated the learning activity by using cooperative learning type rotating trio exchange at material of momentum and impulse; (2) Whether there is or no significant differences between the students’ cooperative skill and whether there is or no significant difference of students’ learning outcomes before and after implementing the rotating trio exchange of cooperative learning; (3) whether there is or no significant correlation between cooperative skill and students’ learning outcomes after implementation of cooperative learning type rotating trio exchange learning model at material of momentum and impulse. The type of research is pre-experimental design. Result finding showed that: (1) There was increase of cooperative skill and learning outcomes of students who participated the learning activity by using cooperative learning type rotating trio exchange; (2)There was significant difference of cooperative skill and learning outcomes of students before and after implementing the rotating trio exchange of cooperative learning; (3) there was no significant correlation between cooperative skill and cognitive learning outcomes, there was no significant correlation between cooperative skill and affective learning outcomes and there was no significant correlation between cooperative skill and psychomotor learning outcomes.